OVERVIEWOF SAFETY AT RAIL-ROAD CROSSINGS IN POLAND IN2008-2018 - Elżbieta MACIOSZEK (Transport Problems, 2020)
The intersection of a public road with a railway line in one level, called a rail-road crossing, is a particularly dangerous place due to the traffic flows crossing it. The regulations give absolute priority to a rail vehicle over a public road user; in addition, significant differences in the masses and speeds of moving vehicles require traffic regulation consisting of adequate passage protection. To this end, the road on which motor vehicles is equipped with road signs informing drivers that they are approaching an intersection with a railway line. The rail-road crossing, depending on thecategory, is equipped with signalingdevices warning of an oncoming train and barriers closing the entire width of the road or part of it, operated or operating automatically. In Poland, the category of rail-road crossing, the associated method and type of security used at the crossing, is determined on the basis of relevant acts and internal regulations of the railway line manager. The paper presents an overviewof the state of safety at rail-road crossings in Poland in the years 2008-2018, presents applicable regulations regarding traffic safety at rail-road crossings,and presents methods of protection of rail-road crossings. In addition, a map of concentration of events on rail-road crossings was presented for the area of the Silesian Voivodeship. The effect of the case study for the Silesian Voivodeship is to identify sensitive rail-road crossings with the highest number of events during the analysis period.